2003
DOI: 10.1007/s00406-003-0430-9
|View full text |Cite
|
Sign up to set email alerts
|

Lithium augmentation therapy in refractory depression?Update 2002

Abstract: Lithium has been used to augment the efficacy of antidepressant medications for more than 20 years. The present study examines whether evidence exists to support the clinical efficacy of lithium augmentation in refractory, treatment resistant depression. Studies were identified by searching Medline (1980 to August 2002) and by scanning the references of published reviews and standard textbooks. Studies were selected if they were open-labeled or double-blind, placebo-controlled or comparator trials that involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 54 publications
0
30
0
2
Order By: Relevance
“…However, lithium has clear utility as an adjunct antidepressant in treatment refractory patients (Heninger et al, 1983). Overall, in placebo-controlled trials, lithium has been found useful as an adjunct medication for 45% of patients (Bauer et al, 2003). Lithium also has antisuicidal effects, the molecular antecedents of which are of considerable interest (Baldessarini et al, 2001;Goodwin et al, 2003;Muller-Oerlinghausen, 2001).…”
Section: Lithium: Past Present and Futurementioning
confidence: 99%
“…However, lithium has clear utility as an adjunct antidepressant in treatment refractory patients (Heninger et al, 1983). Overall, in placebo-controlled trials, lithium has been found useful as an adjunct medication for 45% of patients (Bauer et al, 2003). Lithium also has antisuicidal effects, the molecular antecedents of which are of considerable interest (Baldessarini et al, 2001;Goodwin et al, 2003;Muller-Oerlinghausen, 2001).…”
Section: Lithium: Past Present and Futurementioning
confidence: 99%
“…It has been shown to augment antidepressant effectiveness in treatment-refractory patients Austin et al, 1991). A recent review revealed that approximately 45% of patients monitored in placebo-controlled studies responded to lithium as an adjunct medication for depression (Bauer et al, 2003), a rate higher than for any other medication. Further, some studies have suggested that lithium monotherapy is an effective prophylactic agent in unipolar depressed patients (see for meta-analysis and review).…”
Section: Effect Of Lithium On Human Depressionmentioning
confidence: 99%
“…Furthermore, lithium has clear utility as an adjunct antidepressant in treatment-refractory patients (de Montigny et al, 1983;Heninger et al, 1983). Overall, in placebo-controlled trials, lithium has been found useful as an adjunct medication for approximately 45% of patients (Bauer et al, 2003). However, it is unclear how the clinically relevant antidepressant actions of lithium are exerted.…”
mentioning
confidence: 99%